The crisis in church leadership and the Bible : addressing issues in the practical theology of church leadership through the exegesis of selected portions of the Epistle to Titus - Muller, Julian C. (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2010.